Reflecting on opportunities and challenges regarding implementation of responsible digital agri‐technology innovation. Issue 2 (27th January 2022) - Jakku, Emma; Fielke, Simon; Fleming, Aysha; Stitzlein, Cara
Abstract: Digital transformation within agriculture involves advances in information and communication technologies that promise a 'next generation' of agricultural technologies that will drive improvements in productivity and efficiency while reducing risks and negative impacts. Here, we discuss the Digiscape Future Science Platform, a program that seeks to facilitate the digital transformation of Australia's agricultural industries and land sector. Digiscape is one example of significant efforts internationally to realise the transformative potential of digital agriculture. However, there are significant socio‐ethical challenges associated with digital agriculture. Responsible innovation (RI) provides one conceptual lens to address such challenges, acknowledging the power of research and innovation to create the future and posing questions about the types of futures that societies want to encourage or avoid. This article uses insights from rural sociology and innovation studies, which can complement RI dimensions–anticipation, inclusion, reflexivity and responsiveness–to reflect on how RI can be implemented in digital agriculture initiatives. We draw on insights from interviews with researchers involved in Digiscape to show how RI dimensions can be blended with applied sociological theories and co‐innovation principles and identify recommendations to help foster responsible agricultural technology development.